2020 Computing in Cardiology Conference (CinC) 2020
DOI: 10.22489/cinc.2020.009
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Spontaneous QT Variability Unrelated to RR Variations and Respiration During Graded Orthostatic Challenge

Abstract: The fluctuations of the duration of the electrical activity of the heart, measured as the time distance between Q-wave onset and T-wave end (QT), is under autonomic control. We studied the complexity of the QT variability regulation via the computation of sample entropy of QT variability during sympathetic activation induced by graded head-up tilt. Sample entropy was computed over the original QT series and after factorizing it into partial processes describing QT variability related to heart period, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition to separate estimates of QT/RR hysteresis, i.e., corrections of the RR interval values to be used in QT/heartrate corrections, more complex autoregressive models involve both beat-to-beat RR interval history and QT interval history (Porta et al, 2010(Porta et al, , 2020El-Hamad et al, 2019). These approaches were shown useful in providing estimates of QT interval changes and variability that cannot be explained by heart rate and cardiac period influence (Baumert et al, 2016).…”
Section: Qt/rr Hysteresis Propertiesmentioning
confidence: 99%
“…In addition to separate estimates of QT/RR hysteresis, i.e., corrections of the RR interval values to be used in QT/heartrate corrections, more complex autoregressive models involve both beat-to-beat RR interval history and QT interval history (Porta et al, 2010(Porta et al, , 2020El-Hamad et al, 2019). These approaches were shown useful in providing estimates of QT interval changes and variability that cannot be explained by heart rate and cardiac period influence (Baumert et al, 2016).…”
Section: Qt/rr Hysteresis Propertiesmentioning
confidence: 99%
“…Conversely, methods like heartbeat-evoked potentials have investigated the overall scalp activity response to the heartbeat, serving as an interoceptive measure ( Al et al, 2020 ). Moreover, specific research has delved into BHI representation in the multifractal domain ( Catrambone, Barbieri, Wendt, Abry, & Valenza, 2021 ), as well as the complexity of cerebrovascular joint dynamics ( Catrambone & Valenza, 2023a ; Porta, Cairo, De Maria, & Bari, 2020 ). Recent studies have also focused on detecting microstates (i.e., quasi-stable spatiotemporal states) of brain-heart axis dynamics ( Catrambone & Valenza, 2023b , 2023c ).…”
Section: Introductionmentioning
confidence: 99%
“…QT interval variability without any correction for the RR variability has also been researched (Niemeijer et al, 2014;Baumert et al, 2016;van den Berg et al, 2019) including the reports of normal values in short-term ECG. While such studies might still have included data influenced by the underlying RR variability, physiologically important technical studies were also reported, investigating the QT interval variability with RR interval effects removed by regression modeling (Porta et al, 2010(Porta et al, , 2020El-Hamad et al, 2019). These studies have been based on shorter ECG recordings that allowed QT interval measurements on every beat basis.…”
Section: Introductionmentioning
confidence: 99%